The role of the relative age effect on talent identification in professional road cycling - Voet, J. G.; Lamberts, R. P.; de Koning, J. J.; van Erp, T. (Journal of Sports Sciences, 2022)
This study aims to investigate the presence of the relative age effect (RAE) in (semi-)professional cycling, especially within selecting cyclists for Continental (CT) development teams. Data were collected from www.procyclingstats.com (PCS). Cyclists out of the top-25 countries of the PCS ranking that were part of a CT team between 2005 and 2016 and born between January 1986 and December 1997 were included (n = 2854). Distributions of cyclists in different birth quarters (Q1, Q2, Q3 and Q4) as well as for different starting years at CT level (U23year1, U23year2, U23year3 and U23year4) and reaching professional level or not were investigated using the Chi-square goodness-of-fit test. A RAE was found for cyclists that did not reach professional level, which can be explained by cyclists starting at CT level U23year1 and U23year2 (19 and 20 years old). Meaning that for cyclists at 19 and 20 years old, there is a selection bias towards relatively older (Q1) cyclists at the expense of relatively younger (Q4) cyclists. Within the cyclists that reached professional level, no RAE was found, indicating that the RAE diminishes at professional level. This study provides insight into possible selection errors while selecting cyclists for CT development teams.